The JCMT BISTRO Survey: Unveiling the Magnetic Fields around Galactic Center - Meng-Zhe Yang; Shih-Ping Lai; Janik Karoly; Kate Pattle; Xing Lu; David Eden; Sheng-Jun Lin; Frédérick Poidevin; Ekta Sharma; Jihye Hwang; Lapo Fanciullo; Mehrnoosh Tahani; et al. (The Astrophysical Journal)
We acquired 450 and 850 μ m dust continuum polarization observations toward the inner region of the Central Molecular Zone (CMZ) as part of the B -Fields In Star-forming Region Observations survey using the POL-2 polarimeter on the James Clerk Maxwell Telescope. These observations encompassed three dense structures: the 20 km s ^−1 cloud (20MC), 50 km s ^−1 cloud (50MC), and circumnuclear disk (CND). Our aim is to investigate the magnetic field morphology and strength in the inner region of the CMZ using polarized dust continuum and the Davis–Chandrasekhar–Fermi method. The magnetic field morphology is highly ordered in all three dense regions. The plane-of-sky magnetic field strengths are ∼1 mG for the 20MC and the 50MC, and ∼2 mG for the CND. We compare the energy contributions of turbulence, gravity, and thermal motion with that of the magnetic field using the plasma β , mass-to-flux ratio, and Alfvén Mach number. The outcomes reveal the magnetic field stands out as the predominant factor within the inner region of the CMZ. The dominance of the magnetic field may explain the low star-forming rate in the CMZ. We further investigate the dust grain alignment efficiency by exploring the relationship between polarization fraction and total intensity. The results suggest that dust grains are well aligned with the magnetic fields.